A música como recurso didático na geografia escolar no ensino fundamental - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
The aim of this article is to analyze and understand music as a didactic resource in school geography as an important teaching strategy for the enrichment of the learning teaching process in the 9th grade classes of the Municipal School of Elementary Education Father João Felipe Bettendorff, whose guiding questions were: how can lyrics contribute to the construction of geographic knowledge? How do students evaluate the teacher's discipline and work? And what methodology (s) does the teacher use in the classroom? For that, this research was developed using a qualitative approach with bibliographical and field review, through the questionnaire with closed questions, destined to the students of the class of the 9th Year of Elementary School and semi-structured interview directed to the teacher of the class. The bibliographical and field analyzes indicate that the use of music in the geography discipline is a methodology that can favor the understanding and application of contents in an innovative perspective to contribute to the understanding of the concepts and themes of the geographic contents developed in the classroom. At the same time, it was possible to identify that the students evaluate the use of music as an important methodology to facilitate the understanding of the geographic knowledge and identify the work developed by the teacher as centered in traditional activities such as: a directed study and the classes mostly with use of the textbook. Finally, it is believed that for the teacher to fulfill his role, it is essential to have a degree in Geography, as well as pedagogical knowledge, documents and languages applied to geographic analysis, among these knowledge, music as a tool for the construction and systematization of geographic knowledge.
Keywords: Geografia escolar; Música; Formação de professores; CNPQ:: CIÊNCIAS HUMANAS